P58 Symptomatic improvement in patients with excessive dynamic airway collapse (EDAC) following initiation of positive airway pressure therapy. (11th November 2022) - Shah, NM; Jadeja, K; Cheng, M; Marino, P; Ramsay, M; Srivastava, S; Steier, J; Hart, N; Suh, ES; Murphy, PB; Kaltsakas, G
Abstract : Excessive dynamic airway collapse (EDAC) leads to exertional and nocturnal supine dyspnoea, chronic cough and poor sleep, and is associated with a impact on quality of life (QoL). We sought to determine the effect of positive airway pressure therapy (PAP) on symptoms. We included patients with a computerised tomography (CT) or bronchoscopic diagnosis of EDAC who had received PAP (either nocturnal or ambulatory) for greater than three months. Patients were asked to rate symptom burden including breathlessness at rest and on exertion, orthopnoea and cough frequency on a categorical Likert scale (0=none, 10=worst). They also rated sleep quality and QoL (0=worst, 10=best). Patients provided scores prior to and following the initiation of PAP. Data are presented as mean ± standard deviation. 22 patients (4 male) were included. Age at diagnosis was 54±11 yrs, BMI was 36±8kg·m -2 . Pulmonary function testing demonstrated FEV1 1.6±0.5L (64±26%pred), FVC 2.5±0.7L (80±29%pred), FEV1 /FVC 65±17%, peak expiratory flow 4.5±1.7L/sec (71±27%pred), total lung capacity 5.3±1.3L (100±23%pred), TLCO 6.4±1.5 mmol/min/kPa (82±17%predicted). Eight patients were former smokers. 5/22 patients had previously received bronchoscopic stent insertion as an attempt to treat symptoms, without any improvement. 4% overnight desaturation index was 3±3 evnets/hour. All patients were initiated on nocturnal PAP (adherence 7±2 hrs) and ambulatory continuous PAP with settings of 9±3 cmH2 O. Patients reported an improvement in all symptoms. Symptom scores pre-post PAP initiation: breathlessness at rest (8.4 v 3.8, p<0.001), breathlessness on exertion (8.5 v 4.6, p<0.001), orthopnoea (7.7 v 3.8, p=0.001), cough frequency (8.3 v 3.3, p=0.001), sleep quality (2.5 v 6.8, p=0.002), QoL (2.3 v 7.5, p<0.001). Improvement was reported within days by 75%, weeks by 17% and a year by 8% of patients. Treatment with PAP in patients with EDAC improves respiratory and sleep symptom burden significantly and enhances quality of life. Current international guidelines do not include EDAC as an indication for PAP. Our data demonstrate that PAP should be considered a first-line treatment for patients suffering from symptomatic EDAC.